UPAYA PENERAPAN RETALIASI DALAM PENYELESAIAN SENGKETA PERDAGANGAN INTERNASIONAL MELALUI WORLD TRADE ORGANIZATION (WTO) - Lona Puspita (Fakultas Hukum Universitas Tamansiswa Padang, 2017)
Retaliation as a form of legal protection provided by the WTO against the winning state of the dispute. In practice, retaliation is rarely done by member states. This is because there are many things behind the non-retaliation among WTO members. One possible reason is the high political nuance in retaliation. According to Article 22 of the DSU Agreement of the WTO it is argued that compensation and deferral of concessions or other obligations are temporary measures provided if the recommendations and decisions are not exercised within a reasonable period of time. If the indemnification request can not be executed by the defendant, the plaintiff may take retaliation measures as set forth in article 22 (3) DSU Agreement.